Development of the Smart Tools Proneness Questionnaire (STP-Q): an instrument to assess the individual propensity to use smart tools. Issue 12 (2nd December 2022) - Navarro, J.; Osiurak, F.; Ha, S.; Communay, G.; Ferrier-Barbut, E.; Coatrine, A.; Gaujoux, V.; Hernout, E.; Cegarra, J.; Volante, W.; Hancock, P. A.
Abstract: Humans have developed a prolonged and special relationship with their tools, which themselves exhibit the propensity to become ever more intelligent across the years. A 'smart tool' is defined as to representing any entity, machine, or device that can complete an informational, mechanical, or electronic work. This work explains the development of the Smart Tool Proneness Questionnaire (STP-Q), which is designed to measure an individual's propensity to use smart tools. Data collection was designed to (1) identify the psychological dimensions underlying smart tool use (2) establish the questionnaire's reliability (3) validity, (4) propose a normalisation, and (5) provide an English translation of the French original. The work therefore implements a reliable and valid questionnaire, sensitive to inter-individual differences regarding the propensity to use smart tools. Statistical analysis reveals that the individual self-reported propensity for smart tool use rests on three factors (1) utilitarian use, (2) hedonic and social use, and (3) proneness to delegate. From a theoretical perspective, this individual propensity to use smart tools might be considered key to our species development. In practical terms, measuring an individual's propensity to use smart tools can be of considerable benefit to the design of future smart tools in both professional and non-professional settings. Practitioner summary: The STP-Q, a self-reported measure of an individual's propensity to use smart tools, was developed. STP-Q offers practitioners a measure of individual propensity to use smart tools along three dimensions: utilitarian use, hedonic and social use, and proneness to task delegate. Individual results can easily be interpreted from normalizations that STP-Q provides. Abbreviations: CFI: comparative fit index; GFI: goodness of fit index; IFI: incremental fit index; ISO: International Standardization Organization; IRB: institutional review board of the university of central Florida; IT: information technology; MATB: multi-attribute task battery; NMP-Q: no more phone phobia; RMSEA: root mean square error of approximation; STP-Q: smart tools proneness questionnaire; TAM: technology acceptance model; TRI: technology readiness index; UTAUT: unified theory of acceptance and use of technology; WAIS IV: Wechsler adult intelligence scale